Combined associations of family history and self-management with age at diagnosis and cardiometabolic risk in 86,931 patients with type 2 diabetes: Joint Asia Diabetes Evaluation (JADE) Register from 11 countries - Cheung, Johnny T K; Lau, Eric; Tsui, Cyrus C T; Siu, Edmond L N; Tse, Naomi K W; Hui, Nicole Y L; Mo, Ronald C W; Kong, Alice P S; Fu, Amy; Lau, Vanessa; Jia, Weiping; Sheu, Wayne H H; et al. (BMC, 2022)
Background: Family history (FamH) of type 2 diabetes might indicate shared genotypes, environments, and/or behaviors. We hypothesize that FamH interacts with unhealthy behaviors to increase the risk of early onset of diabetes and poor cardiometabolic control.